2019
DOI: 10.3390/cells8121633
|View full text |Cite
|
Sign up to set email alerts
|

Shaping of Innate Immune Response by Fatty Acid Metabolite Palmitate

Abstract: Innate immune cells monitor invading pathogens and pose the first-line inflammatory response to coordinate with adaptive immunity for infection removal. Innate immunity also plays pivotal roles in injury-induced tissue remodeling and the maintenance of tissue homeostasis in physiological and pathological conditions. Lipid metabolites are emerging as the key players in the regulation of innate immune responses, and recent work has highlighted the importance of the lipid metabolite palmitate as an essential comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 95 publications
0
20
0
Order By: Relevance
“…We hypothesized that the adipocyte micro-environment, might be important regulators in shaping macrophage functions and phenotype. Palmitate induces lipotoxicity with the overproduction of reactive oxygen species (ROS) and when converted to palmitoyl-CoA also serves as a precursor for ceramides generation, which further enhance ROS production [42]. Previous work from our lab showed that palmitic acid stimulated WT lineage negative bone marrow cells but not Tlr4 −/bone marrow cells when directly added to the cells [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesized that the adipocyte micro-environment, might be important regulators in shaping macrophage functions and phenotype. Palmitate induces lipotoxicity with the overproduction of reactive oxygen species (ROS) and when converted to palmitoyl-CoA also serves as a precursor for ceramides generation, which further enhance ROS production [42]. Previous work from our lab showed that palmitic acid stimulated WT lineage negative bone marrow cells but not Tlr4 −/bone marrow cells when directly added to the cells [21].…”
Section: Discussionmentioning
confidence: 99%
“…Palmitate-induced metabolic reprogramming in innate immune cells modulates inflammatory responses and contributes to disease progression [42]. It is critical to investigate the cell type-specific responses of TLR4 to ligands such as palmitate to better understand TLR4's role in SFA-mediated inflammation during obesity.…”
Section: Introductionmentioning
confidence: 99%
“…The transient nature of GCs formation in the regional lymph node requires particular explanations. We presume that certain adipocyte released mediators such as free fatty acids [73] may play a role by triggering unfolded protein response [74] in B cells resulting in enhanced plasma cells and plasmablasts development instead of stable GC persistence [75].…”
Section: Discussionmentioning
confidence: 99%
“…It is well-accepted that the functionality of innate immune cells varies depending on the lipidtype composition of its cytoplasmic membrane. 45,46 Therefore, we evaluated if altered membrane lipid composition of the cKO P2 neutrophils could account for their different migratory ability, by performing high-throughput lipidomic analysis of freshly isolated BMDNs (see supplemental data). However, as there were no significant alterations between the cKO P2 and WT BMDNs (supplemental Figure 2D and Table 3), it appears unlikely that differences in the lipid composition are directly responsible for the dramatic difference in the migratory capacity of the cKOP2 neutrophils.…”
Section: Hif2α Stabilization Upon Loss Of Phd2 Affects Cytoskeletal Gmentioning
confidence: 99%